2012
DOI: 10.4049/jimmunol.1201115
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 1 Is a Biomarker for and Therapeutic Target in Scleroderma-Associated Interstitial Lung Disease That Augments TGF-β1 Signaling

Abstract: Interstitial lung disease (ILD) with pulmonary fibrosis is an important manifestation in systemic sclerosis (SSc, scleroderma) where it portends a poor prognosis. However, biomarkers that predict the development and or severity of SSc-ILD have not been validated, and the pathogenetic mechanisms that engender this pulmonary response are poorly understood. In this study, we demonstrate in two different patient cohorts that the levels of chitotriosidase (Chit1) bioactivity and protein are significantly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 62 publications
1
115
1
Order By: Relevance
“…This dose is markedly lower than those used in adults by others, either by the oral or parenteral route (6,10,12,25). Our previous investigation into the mechanism of curcumin's cytoprotective effect on neonatal lung injury suggested blockade of hyperoxia-induced TGF-␤ activation, which modulates fibroblast differentiation via both canonical (Smad) and noncanonical (MAP kinase) pathways (13,23,33,35). In line with previous observations in a variety of models, we now for the first time document blockade of hyperoxia-induced activation of TGF-␤ and its downstream noncanonical mediator Erk1/2 by curcumin (4,23,26).…”
Section: Discussionmentioning
confidence: 87%
“…This dose is markedly lower than those used in adults by others, either by the oral or parenteral route (6,10,12,25). Our previous investigation into the mechanism of curcumin's cytoprotective effect on neonatal lung injury suggested blockade of hyperoxia-induced TGF-␤ activation, which modulates fibroblast differentiation via both canonical (Smad) and noncanonical (MAP kinase) pathways (13,23,33,35). In line with previous observations in a variety of models, we now for the first time document blockade of hyperoxia-induced activation of TGF-␤ and its downstream noncanonical mediator Erk1/2 by curcumin (4,23,26).…”
Section: Discussionmentioning
confidence: 87%
“…A meta-analysis of 26 studies identified male sex, disease extent on HRCT, presence of honeycombing, elevated Krebs von den Lungen (KL-6) values and increased alveolar epithelial permeability as predictors of both mortality and ILD progression in unadjusted analysis, while disease extent on the HRCT scan was the only variable that independently predicted both mortality and ILD progression [39]. Recently, a loss of density on capillaroscopy was shown to be associated with worse FVC and DLCO [40] and biomarkers that correlate with the severity of fibrosis have been proposed: elevated levels of chitinase [41], tenascin C [42], growth differentiation protein 15 [43], cartilage oligomeric matrix protein, alveolar epithelial cell antigen, KL-6 [44] and the chemokine CXCL4 [45]. Serum IL-6 predicted early disease progression and IL-6 values >767 pg·mL −1 were predictive of risk of death within the first 30 months in patients with mild SSc-ILD [46].…”
Section: The Outcome and Its Predictorsmentioning
confidence: 99%
“…Studies with genetically modified mice demonstrated that CHIT1 enhances TGF-β1 receptor expression and signaling, suggesting a role in initiating or amplifying the response to organ injury [58]. In addition, it was demonstrated that heterozygosis for a 24-bp duplication in the CHIT1 gene protects from nonalcoholic fatty liver disease progression [59].…”
Section: Chit1 and Dmmentioning
confidence: 99%